Enhancing the Capacity of Roemah Djoempoetan Srihadi SME through Socialization of Financial Risk Management Literacy - Jannah, Luluul; Pronosokodewo, Baniady Gennody; Nirbita, Betanika Nila; Norviana, Syahida; Buchori, Willa Putri Malinda (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This community service initiative addresses the identified gap between theoretical understanding and practical application of financial risk management in the Roemah Djoempoetan Srihadi SME, a cultural enterprise in Yogyakarta specializing in jumputan and batik products. Despite the SME's recognized cultural value and participation in government mentoring programs, initial interviews revealed critical vulnerabilities: a complete absence of financial risk measurement, inadequate financial record-keeping, and high dependency on consignment sales models. These shortcomings render the business susceptible to capital depletion, revenue instability, and impediments to sustainable growth. The intervention employed a two-pronged methodology comprising targeted socialization sessions on financial risk management literacy and direct mentoring. The program focused on implementing practical solutions, including diversifying sales channels through e-commerce platforms, simplifying financial recording using user-friendly applications, and strengthening policy advocacy through MSME associations. The outcomes demonstrate that a comprehensive approach integrating financial literacy with strategic business adjustments significantly enhances operational resilience. This initiative underscores the necessity of transitioning culturally significant SMEs from production-centric hobbies to professionally managed enterprises, thereby ensuring the dual sustainability of both the business entity and the local cultural heritage it represents.